Dietary Diversity and Nutritional Status of the Oraon Tribal Women: An Anthropometric Measurement Approach - Seema Kujur; Barua, Sukanya; Manjeet Singh Nain; Subhashree Sahu; V. Sangeetha; KV Praveen; Girish Kumar Jha; Rajat Kumar Nath; Manichandana Gudla (Indian Journal of Extension Education, 2025)
The study was conducted among the Oraon tribal women of Chhota Nagpur Plateau, comprising Jharkhand and Chhattisgarh, during 2024-25. Using multi-stage random sampling, 400 respondents were selected. The data concerning dietary diversity was collected using a structured interview schedule. Anthropometric measurement tools, including BMI and MUAC, were employed to measure nutritional status. Only 22% of the respondents met the minimum dietary diversity criteria, and 78% of women had an inadequate nutritional intake, eating less than five defined food groups. A Welch’s ANOVA test highlighted significant variation in dietary intake across selected districts. Only 37.75% of the women had normal BMI, whereas 48.75% were affected by chronic energy deficiency, and a transition towards obesity was evident. 73.50% of women were in the undernutrition category, defined by a MUAC cut-off below 22.8 cm. A comparison of nutritional status across selected districts highlighted no significant difference. The Pearson correlation analysis indicated a significant positive relationship between BMI and MUAC. The findings highlighted the efforts to address malnutrition in Oraon tribal women and enhance women’s nutritional outcomes through kitchen gardening, nutrition-sensitive agriculture, and effective implementation of government nutrition programs.